Association between metabolic phenotype and urinary albumin‐creatinine ratio in Chinese community adults: A cross‐sectional study. Issue 8 (30th August 2022) - Zhang, Yue; Li, Binqi; Liu, Yang; Gao, Wenxing; Chen, Kang; Wang, Anping; Tang, Xulei; Yan, Li; Luo, Zuojie; Qin, Guijun; Chen, Lulu; Wan, Qin; et al.
Abstract: Background: Urinary albumin‐creatinine ratio (UACR) is a sensitive marker of kidney injury. This study analyzed the prevalence of different metabolic phenotypes and investigated their relationship with UACR in Chinese community adults. Methods: This study involved 33 303 participants over 40 years old from seven centers across China. They were stratified into six groups according to their body mass index (BMI) and metabolic status: metabolically healthy normal weight (MHNW), metabolically healthy overweight (MHOW), metabolically healthy obesity (MHO), metabolically unhealthy normal weight (MUNW), metabolically unhealthy overweight (MUOW), and metabolically unhealthy obesity (MUO). Increased albuminuria was defined as a UACR ≥30 mg/g. Results: The percentages of MHNW, MHOW, MHO, MUNW, MUOW, and MUO were 27.6%, 15.9%, 4.1%, 19.8%, 22.5%, and 9.6%, respectively. Multiple logistic regression analysis showed that the MHO group (odds ratio [OR] 1.205; 95% CI, 1.081‐1.343), MUNW group (OR 1.232; 95% CI, 1.021‐1.486), MUOW group (OR 1.447; 95% CI, 1.303‐1.607), and MUO group (OR 1.912; 95% CI, 1.680‐2.176) were at higher risk of increased albuminuria compared to the MHNW group. Subgroup analysis indicated that the risk of increased albuminuria was further elevated among regular smokers in men aged 40 to 55 years old with abdominal obesity. Conclusions: Among Chinese community adults, increased albuminuria was associated with increased BMI whether metabolism was normal or not, and those with abnormal metabolism were at greater risk of increased albuminuria than those with normal metabolism. These findings suggest that overweight or obesity or metabolic abnormalities are risk factors for chronic kidney disease. Abstract : Highlights This is the first multicenter, large‐sampled cross‐sectional study of the association between different metabolic phenotypes and urinary albumin‐creatinine ratio (UACR) in Chinese community adults. Our study may be helpful for people with increased albuminuria. We recommend that they have their UACR checked regularly and maintain a healthy lifestyle to reduce their risk of chronic kidney disease. 摘要: 背景: 尿白蛋白/肌酐比值(UACR)是反映肾脏损伤的有效指标。本研究分析了不同代谢表型在中国社区成人中的患病率, 并探讨了它们与UACR的关系。 方法: 这项研究纳入来自中国7个中心的33303名40岁以上的参与者。根据体重指数(BMI)和代谢状态将受试者分为6组:代谢健康正常体重(MHNW), 代谢健康超重(MHOW), 代谢健康肥胖(MHO), 代谢不健康正常体重(MUNW), 代谢不健康超重(MUOW)和代谢不健康肥胖(MUO)。UACR≥ 30 mg/g被定义为蛋白尿增加。 结果: MHNW, MHOW, MHO, MUNW, MUOW和MUO所占比例分别为27.6%, 15.9%, 4.1%, 19.8%, 22.5%和9.6%。多因素Logistic回归分析显示, MHO组(OR=1.205[95%CI:1.081 1.343]), MUNW组(OR=1.232[95%CI:1.021 1.486]), MUOW组(OR=1.447[95%CI:1.303 1.607])和MUO组(OR=1.912[95%CI:1.680 2.176])发生蛋白尿增加的风险高于MHNW组。亚组分析表明, 在40至55岁腹部肥胖的男性中, 经常吸烟的人蛋白尿增加的风险进一步增加。 结论: 在中国社区成年人中, 无论代谢是否正常, 尿白蛋白增加都与BMI增加相关, 代谢异常的人比代谢正常的人更容易出现蛋白尿增加的危险。这些发现表明, 超重, 肥胖和代谢异常是慢性肾脏疾病的风险因素。